'A picture of who we are as a family': conceptualizing post‐adoption contact as practices of family display. (14th July 2015) - MacDonald, Mandi
Abstract: Social work has a central role in negotiating and supporting birth family contact following adoption from care. This paper argues that family display (Finch) offers a useful conceptual resource for understanding relationships in the adoptive kinship network as they are enacted through contact. It reports on an interpretative phenomenological analysis of adoptive parents' accounts of open adoption from care that revealed direct and indirect contact to be contexts in which they and birth relatives performed family display practices: communicating the meaning of their respective relationships with the adopted child and seeking recognition that this was a legitimate family relationship. The analysis explores how family display was performed, and the impact of validating or invalidating responses. It aims to illuminate these social and interpretive processes involved in adoptive kinship in order to inform social work support for contact. The findings suggest that successful contact may be promoted by helping adoptive and birth relatives validate the legitimacy of the other's kin connection with the child, and through arrangements that facilitate family‐like interactions.